Functions of Speech Acts in â€œCritical Elevenâ€ - Ida Ayu Putu Arini Dewi; I Nyoman Kardana; I Nyoman Muliana (Program Studi Magister Ilmu Linguistik Universitas Warmadewa, 2020)
This study aims to examine the speech act functions found in the â€œCritical Elevenâ€ film and reveal the conversational implicatures used by the film actors. To actualise this aims, this study was conducted using qualitative research designs and by making the speech act theory of (Levinson, 1983) and the speech act function theory of Searle (1979) as the basis for examining the speech act functions in the said film according to its type. The data were collected using the simak method, a method similar to observation one accompanied by an act of scrutinizing speeches of the actors in the film â€œCritical Elevenâ€. The oral data were collected from the conversations then transcribed into written data. The data analysis result are presented informally or descriptively. The results of data analysis showed there are five speech act functions in the film, namely representative, directive, commissive, expressive, and declarative. The representative function is manifested in the act of giving witness, acknowledging, and stating. The directive one includes the act of asking, and urging. Commissive function includes expressing abilities and promising. Expressive function includes blaming, praising, and congratulating. Declarative function is manifested in the act of prohibiting. Examining the function and meaning of speech acts in the film â€œCritical Elevenâ€ from the perspective of sociolinguistics is an important topic to raise in further research.